UTILIZING CLUSTERING TECHNIQUE TO ENHANCE STUDENTS’ ENGLISH WRITING PERFORMANCE - Erina Ayu Lestari; Budiarti Budiarti; Juhansar Juhansar (University of Kuningan, 2022)
This present study aims at exploring the utilization of the clustering technique to enrich students’ performance in writing a descriptive text in English, discovering students’ participation in learning-teaching descriptive text writing using the clustering technique, and finding out the improvement of students’ English writing performance using the clustering technique. This research implies a Mixed-Method Action Research design where researchers act as teachers. The respondents consisted of 30 Vocational High School students. This research uses qualitative and quantitative data. The qualitative data were obtained by observing the learning-teaching process of writing descriptive text using the clustering technique and interviewing students. Quantitative data were acquired through the pre-test, post-test I, and post-test II. The results show that implementing the clustering technique in the learning-teaching process enriches students’ performance and attracts students’ participation, attention, activeness, motivation, and seriousness in learning English writing. Pre-test and post-tests prove that the clustering technique enhances students’ English writing performance. The technique helps students to express ideas in English text writing. Students gain 67.49 in the pre-test, up to 75 in the post-test I, and up to 79.87 in the post-test II. The mean improvement percentage shows about 16.6% enhancement from the pre-test, 36.6% from the post-test I, and 86.6% from the post-test II.